Hubungan Pola Asuh Orang Tua Dengan Perilaku Temper Tantrum Pada Anak Usia Prasekolah - Aula Fitri Ayuningrum; Indra Tri Astuti; Herry Susanto (Journal of Health, Medical, and Psychological Studies, 2026)
This study examined the relationship between parenting styles and temper tantrum behavior among preschool children at TK PGRI 87 Semarang. A quantitative correlational analytic design with a cross-sectional approach was employed. The population consisted of all parents or guardians of preschool children, and total sampling was applied, yielding 30 respondents. Data were collected on 15 November 2025 using two validated Likert-scale questionnaires: a 30-item parenting style instrument and a 33-item temper tantrum instrument. Validity coefficients ranged from 0.612–0.820 for parenting style and 0.617–0.959 for temper tantrum, while reliability testing produced a Cronbach’s Alpha of 0.812. Univariate analysis described respondent characteristics and variable distributions, while bivariate analysis used Spearman’s Rank correlation due to ordinal data. The results demonstrated a statistically significant relationship between parenting style and temper tantrum behavior (p = 0.003; α = 0.05). Authoritarian and permissive parenting were more frequently associated with moderate to high tantrum levels, whereas democratic parenting was linked to lower tantrum intensity. These findings highlight parenting style as a key determinant of emotional regulation development in preschool children.